'A movement that renovates people, as well as buildings': squatting and neodomestic space in Seth Tobocman's War in the Neighborhood. Issue 7 (3rd July 2022) - Hines, Frankie
ABSTRACT: Seth Tobocman's War in the Neighborhood (2000), a graphic narrative about squatting in Manhattan's Lower East Side, attempts to rethink the politics (both oppressive and liberatory) of domestic space. This article examines the meanings of home in War in the Neighborhood in the terms suggested by Kristin J. Jacobson, whose theorisation of 'neodomestic fiction' suggests a move in contemporary American literature toward representations of domesticity that affirm a productive instability . This instability is made manifest in Tobocman's work on the terrain of gender and race, where attempts to practice an anarchistic prefigurative politics collide with the recurrence of misogyny and racism to destabilise domestic spaces that are already threatened by the gentrification of the neighbourhood. Tobocman depicts the squats as spaces motivated by efforts to put radical politics into practice, but acknowledges the perils they encounter in doing so, and develops an account of the workings of power that provides an explanation. After describing the multivalent accounts of home that occupy a central role in contemporary U.S. politics, I examine the contestations that destabilise domesticity in War and argue that the text, by virtue of its political emphasis and urban preoccupation, highlights connections between neodomestic fiction and critical literary geography.